1. DEGREE OF SUPERIORITY IN AIR OPERATIONS THEORETICAL ANALYSIS, DETERMINING FACTORS, AND STRATEGIC CASE STUDY - Andri Gandhy; Suroso; Ronny; Samsul Bahri; Muchammad; Dikatama Tsania; Supriyanto Kemal; Kusuma Safarie (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to analyze the degree of air superiority, a strategic concept thatplays a central role in the planning and implementation of modern air operations. This termrefers to the degree of control of an air force over a specific area that allows the execution ofmissions without significant interference from opposing air forces. In general, the degree of airsuperiority is classified into three categories: air parity, air superiority, and air supremacy, eachof which indicates a different degree of dominance over potential enemy air threats. Airdominance is a strategic prerequisite that determines the outcome of modern conflicts. Theconcept of degree of superiority evolves along with changes in technology, doctrine, and thecomplexity of global geopolitics. In the context of air operations, achieving degree of airsuperiority is influenced by various factors, including technological capabilities, theeffectiveness of air defense systems, information mastery, and the efficiency of command,control, communications, computers, intelligence, reconnaissance, and surveillance (C4ISR)systems. The interaction of these factors contributes to the success of joint operations and theability to maintain long-term air dominance. Effective air superiority also directly impacts thefreedom of action of one's own forces in conducting cross-service operations. Acomprehensive understanding of the degree of air superiority is a key factor in strategicdecision-making at the operational level. Integration of technological capabilities, informationsuperiority, and cross-service coordination is necessary to achieve sustainable air dominance.Therefore, analyzing the degree of air superiority is not only crucial for tactical purposes butalso serves as the basis for developing comprehensive air defense doctrine and strategy. Thisarticle discusses the theoretical framework in depth, the factors influencing its achievement,and presents case studies from various conflicts ranging from World War II to potential conflictsin the Indo-Pacific. This study confirms that successfully achieving air superiority depends notonly on air power alone, but also on multi-domain integration, defense industry readiness, andpolitical and diplomatic support.